An Implementation of Patient Safety Program at Hospital Royal Prima Medan in 2021 - David Calvin; Chrismis Novalinda Ginting; Sri Wahyuni Nasution (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to know and analyze the implementation of the Patient Safety program and the factors that influence it at the Royal Prima Hospital Medan in 2021. This research is a mixed methods research that is a combination of qualitative and quantitative research. The research informants consisted of 1 person from the hospital health committee, 1 head of the inpatient ward, and 4 implementing nurses in the inpatient ward. The population is all implementing nurses in the inpatient rooms as many as 319 people. the sample was taken using the Taro Yamane formula for as many as 76 people. Data collection techniques through interviews, questionnaires, and documentation. Data analysis methods consist of qualitative analysis with descriptive methods and quantitatively using univariate, bivariate, and multivariate analysis using p multiple linear regression equation. The results of the study that the implementation of the patient safety program at the Royal Prima Hospital Medan in 2021 is quite good; there is an influence of the knowledge, attitude, workload, and supervision of the head of the room on the implementation of the Patient Safety program at the Royal Prima Hospital Medan in 2021.